2018
DOI: 10.1007/s11356-018-2537-6
|View full text |Cite
|
Sign up to set email alerts
|

Properties and effects of organic additives on performance and emission characteristics of diesel engine: a comprehensive review

Abstract: Fast depletion of conventional automobile fuels and environmental pollution due to exhaust emission are the issues of great importance. Improvement in engine performance and emission control is quite difficult to handle simultaneously. The fuel properties can be improved substantially by incorporation of additives in different proportions to get better emission standard without deteriorating the engine performance. The aim of current study is to review/summarize the effects of various organic additives on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(6 citation statements)
references
References 148 publications
0
6
0
Order By: Relevance
“…It is observed that E100 blend shows more BTE compared to the rest of ethanol blends and pure diesel mode engine. BTE may increase due to lower heat losses in the cylinder because pure ethanol has a lower flame temperature compared to the remaining ethanol blend and diesel (Kumar et al , 2018).…”
Section: Resultsmentioning
confidence: 99%
“…It is observed that E100 blend shows more BTE compared to the rest of ethanol blends and pure diesel mode engine. BTE may increase due to lower heat losses in the cylinder because pure ethanol has a lower flame temperature compared to the remaining ethanol blend and diesel (Kumar et al , 2018).…”
Section: Resultsmentioning
confidence: 99%
“…From the results, CO emission decreases with a rise in the load on the engine. For full load condition on the engine, that is, 12 is about 0.029 vol% lower than neat diesel, which is a net reduction of 52.72%. This is followed by 50Mg W/D 10, 75Al W/D 10, and 50Mg 50Al W/D 10 which have a similar value range of 0.027 vol% and this is a significant 50.91% reduction in CO level which is lower compared with neat diesel.…”
Section: Characteristics Of Emission Of the Enginementioning
confidence: 97%
“…Results show that at the injection pressure 220 bar, the NO x , CO, HC, and smoke emissions are decreased, and as well as other combustion factors, including the eat release rate (HRR), gas temperature, and cylinder pressure mass fraction, are also improved when the proposed fuel is used. kumar et al 12 have addressed environmental pollution and diesel engine emissions as problems for environmental degradation. And hence author has reviewed different types of nanoparticle‐added biodiesel for better performance, efficiency, and to reduce exhaust emissions.…”
Section: Introductionmentioning
confidence: 99%
“…By blending DEE with diesel, HC and CO may be reduced. Methoxyethyl ether additives are renewable bio-fuels which generally produce by the reaction of isomyelin and isobutene with ethanol [10]. It can burn mainly and easily consist of diethyl ether (DEE), 2-Methoxyethyl ether (MXEE), 2-ethoxyethyl ether (EXEE), dimethyl ether (DME), Teramylethyl ether (TAEE), ethyl ter-butyl ether (ETBE), di-n-butyl ether (DNBE), etc.…”
Section: Introductionmentioning
confidence: 99%